Fate and destiny according to Ibn al-Attar and the actions of servants as a model through his book “Pure Belief”: an analytical study - Mustafa, Asst. Prof. Dr. Khaled Ahmed Mustafa; Mohammad, Amanj Jafar Muhammad (Sulaimani Journal for Humanities, 2025)
Imam Ibn Al-Attar was a prominent figure in the eighth century AH, whose commendable efforts and righteous works supported this religion and defended it. Fate and destiny with their four pillars - knowledge, knowledge, will, and creation - are a pillar of faith, and a servant's faith is not complete without them. The actions of the servants are attributed to Allah in terms of creation and incorporation, and to the servants in terms of action and acquisition, and there is no contradiction between them. This is the saying of the early Muslims. The Jabriyah claim that the servants have neither power nor choice due to the comprehensiveness of Allah's creation and will over all things. Rather, the servants are driven and have neither power nor will. The Qadariyah deny predestination, and they are of two groups: the extremists who deny Allah's foreknowledge of events and believe that the servant creates his actions independently. The less extremists believe in the latter but not the former.
Keywords: Predestination (Qadar); Fate and Destiny; Islamic Theology (Aqeedah); Free Will in Islam